HEP Event Management and Promotion Application - arsahak, hakim; Zainal, Nurezayana (Applied Information Technology And Computer Science, 2026)
Universiti Tun Hussein Onn Malaysia (UTHM) faces challenges in sharing event information because details are scattered across platforms, making it hard for students to stay informed and reducing campus participation. This project aims to create a mobile app that centralizes event information and improves student engagement. The app is developed using a prototyping approach, which involves collecting user needs, designing, creating a prototype, gathering feedback, and refining the system. The app features include user registration, an event calendar, real-time updates, notifications, and tools for event organizers to manage events and track their performance. Early results show the app helps students easily find and join events, improving participation and creating a more connected campus. Future improvements could include adding personalized features and better analytics to make the app even more useful, supporting UTHM’s goal of using digital tools to enhance campus life